Synthesis of Silver Nanoparticles with Reductant of Java Long Pepper Leaf Extract (Piper Retrofractum Vahl) and Its Application as a Mercury Detector - Muhamad Allan Serunting; Prio Santoso; Indah Puspita Sari; Riyanto Widodo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
The synthesis of silver nanoparticles using the green chemistry concept utilizing Java long pepper leaf extract as a reducing agent has been successful. Silver nanoparticles were synthesized under optimum 1 mM silver nitrate concentration, 250 μL Java long pepper leaf extract, and 30 minutes under sunlight radiation. The silver nanoparticles formed can be confirmed by the change in the color of the solution from colorless to brownish red, indicating a reduction of Ag+ to Ag0. The Uv-vis spectrum showed a peak Surface Plasmon Resonance (SPR) at 441 nm. The FTIR spectrum showed that functional groups' vibrations in the Java Chili Leaf extract confirm that the phenol, alkaloid, and flavonoid compounds present in the extract act as reducing agents. TEM images show spherical silver nanoparticles with an average diameter of 17.65 nm. The potential of silver nanoparticles to detect Hg (II) metal is evidenced by a decrease in the color intensity of the silver nanoparticle solution along with the increasing concentration of Hg (II), which reacts back-oxidizing Ag0 to Ag+. The value of the correlation coefficient of the linear equation is 0.9807.